FAULT COMPACTION AND OVERPRESSURED FAULTS: RESULTS FROM A 3-D MODEL OF A DUCTILE FAULT ZONE - Fitzenz D.D.; Miller S.A. (My University, 2003)
A model of a ductile fault zone is incorporated into a forward 3-D earthquake model to better constrain fault-zone hydraulics. The conceptual framework of the model fault zone was chosen such that two distinct parts are recognized. The fault core, characterized by a relatively low permeability, is composed of a coseismic fault surface embedded in a visco-elastic volume that can creep and compact. The fault core is surrounded by, and mostly sealed from, a high permeability damaged zone. The model fault properties correspond explicitly to those of the coseismic fault core. Porosity and pore pressure evolve to account for the viscous compaction of the fault core, while stresses evolve in response to the applied tectonic loading and to shear creep of the fault itself. A small diffusive leakage is allowed in and out of the fault zone. Coseismically, porosity is created to account for frictional dilatancy. We show in the case of a 3-D fault model with no in-plane flow and constant fluid compressibility, pore pressures do not drop to hydrostatic levels after a seismic rupture, leading to an overpressured weak fault. Since pore pressure plays a key role in the fault behaviour, we investigate coseismic hydraulic property changes. In the full 3-D model, pore pressures vary instantaneously by the poroelastic effect during the propagation of the rupture. Once the stress state stabilizes, pore pressures are incrementally redistributed in the failed patch. We show that the significant effect of pressure-dependent fluid compressibility in the no in-plane flow case becomes a secondary effect when the other spatial dimensions are considered because in-plane flow with a near-lithostatically pressured neighbourhood equilibrates at a pressure much higher than hydrostatic levels, forming persistent high-pressure fluid compartments. If the observed faults are not all overpressured and weak, other mechanisms, not included in this model, must be at work in nature, which need to be investigated. Significant leakage perpendicular to the fault strike (in the case of a young fault), or cracks hydraulically linking the fault core to the damaged zone (for a mature fault) are probable mechanisms for keeping the faults strong and might play a significant role in modulating fault pore pressures. Therefore, fault-normal hydraulic properties of fault zones should be a future focus of field and numerical experiments.
Keywords: EARTHQUAKE MECHANICS; FAULT MODELS; PERMEABILITY; SEISMICITY; VISCOELASTICITY